Influence of centrifugal force on the release kinetics of growth factors in platelet-rich and leukocyte-rich fibrin network in healthy humans (Research, Society and Development, 2022)
Dentistry is increasingly advanced in the use of biomaterials in various areas of activity. Platelet-rich fibrin (PRF) is an example of this advance, but despite this, there are still many gaps regarding the full biological potential of this material. The crucial issue for the quality, applicability and function of PRF is linked to the way in which this material is obtained. Changes in the centrifugation process can change the composition of this biomaterial and also its form of tissue activation. The aim of this study was to evaluate the influence of velocity and centrifugal force on the kinetics of growth factor release by human PRF. Materials and methods: For the development of the study, peripheral blood samples from healthy patients were used and this material was subjected to three protocols with different centrifugation forces: 400g, 800g and 200g. The PRFs obtained were grown in sterile cell culture medium and evaluated at times: 15 minutes, 1 day, 3 days and 7 days. Growth factors were detected by the ELISA method and quantified in all protocols. From the results obtained, it was seen that only the growth factor EGF showed significant differences (p=0.044) in changes in centrifugal force at the times evaluated. The other factors showed changes in detection over the days. Conclusion: These variations in the protocol do not interfere in the detection of most growth factors, which gives the professional confidence in obtaining the potential of the material, even with small variations in its processing form.